Is It Still Prohibited to Perform Spinal Anesthesia in Patients with Advanced Heart Disease? - Maryam Vosoughian; Shide Dabir; Faramarz Mosaffa (Archives of Anesthesia and Critical Care)
Spinal anesthesia is generally prohibited in patients with severe valvular heart disease (e.g. severe aortic stenosis), cardiomyopathies and heart failure concerning the hemodynamic effects of sympathetic system blockade in patients with limited cardiac output. Intrathecal single injection of low doses of local anesthetic  in combination with low dose short acting opioids can be administered safely in lower abdominal and lower limb surgeries lasting 60 to 90 minutes . In longer surgeries, epidural catheters can be inserted through the epidural needle into the intraspinal space and intermittently administered low doses of local anesthetic plus low doses of fentanyl or sufentanil as needed.